2017
DOI: 10.3233/bme-171710
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cellulose membrane used as biological dressings on third-degree burns in rats

Abstract: Thus, was concluded that the bacterial cellulose-based biomaterial both in its pure state and enriched with lidocaine optimizing the full-thickness burn wound healing in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Our study evaluated the fourth day after the wounding and observed COX-2 expression in all groups, corresponding to its physiological response to the inflammatory process [35][36][37][38][39]. The CG group showed the higher immunolabeling, suggesting that the proposed treatments, isolated or in association, had positive effects in this immunoexpression and improved the resolution of the inflammatory phase.…”
Section: Discussionmentioning
confidence: 75%
“…Our study evaluated the fourth day after the wounding and observed COX-2 expression in all groups, corresponding to its physiological response to the inflammatory process [35][36][37][38][39]. The CG group showed the higher immunolabeling, suggesting that the proposed treatments, isolated or in association, had positive effects in this immunoexpression and improved the resolution of the inflammatory phase.…”
Section: Discussionmentioning
confidence: 75%
“…Their results indicated that the use of bacterial cellulose dressings with and without lidocaine had comparable advanced repair outcomes, with both being more effective than the untreated control group. Skin appendages, mild inflammatory cell influx, collagen fiber organization and mild immunostaining were observed [26].…”
Section: Cellulosementioning
confidence: 99%
“…Tactile sensor (simultaneous sensing of temperature and pressure) [126] Strain-sensing protonated aerogels from cellulose nanofibrils [127] Drug delivery Peroral Paracetamol [49] Ibuprofen (colonic release) [70] Methotrexate (colonic release) [128] Transdermal Analgesics, antiphlogistics, corticoids, antihypertensives [50,51] Diclophenac [129] Propranolol [130] Topical Local anesthetics [131] Antiseptics [132,133] Antibiotics (gentamycin, ceftriaxone) [33,43] Antibacterial peptides [134] Other antimicrobial, antiinflammatory and antitumor drugs [135,136] 183…”
Section: Lithium Batteriesmentioning
confidence: 99%